Bioavailability, pharmacokinetics and tissue residues of cephradine (Atocef ForteÂ®) in healthy and colisepticemic broiler chickens - Aboubakr, Mohamed; Elbadawy, Mohamed (International Journal of Pharmacology and Toxicology, 2017)
The pharmacokinetics (after single intravenous and oral dose) and tissue residues (orally and daily for five days) of cephradine (20 mg/kg b.wt.) were investigated in healthy and experimentally E.coli infected broiler chickens. Following single intravenous injection to healthy chickens, cephradine obeyed a two compartments open model and the elimination half-life (t1/2Î²), volume of distribution (Vdss) and total body clearance (CLtot) of cephradine were 2.93 h, 321.5 ml/kg and 0.08 L/h/kg, respectively. Following single oral administration of cephradine to healthy chickens, the peak serum concentration (Cmax) of it was 26.7 Âµg/mL and achieved (Tmax) at 2.41 h. The oral bioavailability of cephradine was 87.7%. Cephradine was assayed in kidney, liver, heart, gizzard, spleen, breast muscle, thigh muscle and skin after 24, 48, 72, 96 and 120 h after last dose. On conclusion, cephradine is a good choice for treatment of colisepticemia in chickens due to its higher oral bioavailability and distribution.